IMPACT OF CULTIVARS, PLANTING DATES AND CHICKEN MANNERS ON VEGETATIVE GROWTH AND YIELD OF ONION (ALLIUM CEPA L.) - ABABAKER, SHIREEN KHUDHER; MOHAMMED, GHURBAT HASSAN (Journal of Duhok University, 2022)
The study was examined the effects of three planting dates (1st October, 15th October, and 1st November) and three levels of chicken manures (0, 1000, and 1500 g.m-1) on two cultivars of onion (Texas Early white and Early white Grano) during the growth season 2021–2022 at the vegetable research farm of the Protected Cultivation Department, Zakho Technical Institute/Dohuk Polytechnic University. The results showed that there were no significant differences between two cultivars in all traits excepted the cultivar Texas was superior over cultivar Grano in number of leaves plant-1. Planting date at 1st October led to significant differences in plant length (cm), number of leaves plant-1, mean bulb weight (g), number of stored leaves bulb-1, total yield (t.ha-1), N%, P%, K% and S% in bulbs. Application chicken manures especially 1000 g.m-1 significantly increased all traits. The combination among (cultivar Texas, 1st October planting date and 1000 g.m-1 chicken manure significantly enhanced the plant length (66.14 cm), number of leaves plant-1 (18.18), mean bulb weight (328.51 g), number of stored leaves bulb-1 (13.11), total yield (38.55 t.ha-1), N% (2.64%), P% (0.432%), K% (4.32%) and S% (0.661% in bulbs